Quick-setting environment-friendly high-strength cement and preparation process thereof
By introducing modified phosphorus slag, quick-setting agent, additive and azobisisobutyronitrile into the cement clinker, and using the cross-linking effect of modified fibers and cyclodextrin MOF, the contradiction between cement speed-setting and mechanical properties is solved, and the preparation of high-strength and environmentally friendly cement is achieved.
Patent Information
- Application Number
- CN202411570503.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-06
AI Technical Summary
After the existing cement has improved its fast-setting properties, its compressive and flexural strength are generally low, and the comprehensive utilization rate of phosphorus slag is not high, which affects environmental protection.
By calcining limestone, high silica, iron, aluminum material and phosphorus slag into cement clinker, and on this basis, modified phosphorus slag, quick-setting agent, additive and azobisisobutyronitrile are added. The silicon sol modification of the modified phosphorus slag and thiosilane coupling agent are treated with the introduction of modified fibers and cyclodextrin MOF, the rapid-setting and mechanical strength of cement are promoted.
The high-strength and environmentally friendly characteristics of cement are achieved, the compression and flexural strength of cement is improved, and the phosphorus slag is effectively utilized, reducing the stacking of industrial waste slag and environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement, in particular to a quick-setting, environment-friendly, high-strength cement and a preparation process thereof. Background Art
[0002] As an inorganic cementitious material, cement is widely used in the fields of construction, water conservancy, transportation, national defense, etc. At present, the accelerated construction of railway modernization infrastructure has promoted the demand for basic raw materials such as cement, and the performance requirements for basic raw materials such as cement are also gradually increasing. Among them, cement used in railways and other places generally requires low alkalinity, and the main material is generally calcined clinker, which generally needs to deal with accelerators to promote its coagulation. However, accelerators are usually introduced to improve hydration performance; however, the compressive and flexural strengths after rapid setting are generally low. Therefore, it is necessary to further improve the mechanical properties of this type of cement and enhance its practical applicability.
[0003] On the other hand, the accumulation of phosphorus slag has increased in recent years, but the comprehensive utilization rate is not high, which is not conducive to environmental protection. Among them, the main component of phosphorus slag is calcium substances, which can be used as an admixture in cement to promote waste utilization and enhance environmental protection. However, its direct introduction into cement will affect the rapid setting and mechanical properties of cement, and its practical applicability needs to be further optimized.
[0004] In summary, solving the above problems and preparing a fast-setting, environmentally friendly, high-strength cement has important application value. Summary of the invention
[0005] The purpose of the present invention is to provide a fast-setting, environmentally friendly, high-strength cement and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation process of quick-setting environmentally friendly high-strength cement comprises the following steps: Step 1: Grind and mix limestone, high silica, iron material, aluminum material, and phosphorus slag to obtain raw material; calcine the raw material, cool it, and obtain cement clinker; Step 2: Grind and mix cement clinker, modified phosphorus slag, accelerator, additive and azobisisobutyronitrile to obtain high-strength cement.
[0007] More optimally, the calcination process parameters are: heating to 800-1000°C at a rate of 40-50°C / min, calcining for 10-30 minutes; heating to 1150-1250°C at a rate of 20-30°C / min, and continuing calcining for 10-15 minutes.
[0008] More optimally, the raw materials of the cement clinker include the following components: by weight, 78-82 parts of limestone, 10-13 parts of high silica, 2-5 parts of iron materials, 1.5-3 parts of aluminum materials, and 3-4 parts of phosphorus slag.
[0009] More optimally, the high-strength cement comprises the following raw materials: by weight, 72 to 80 parts of cement clinker, 10 to 15 parts of modified phosphorus slag, 2 to 3 parts of accelerator, 8 to 10 parts of additives, and 0.05 to 0.06 parts of azobisisobutyronitrile.
[0010] More optimally, the preparation method of the modified phosphorus slag is: adding yellow phosphorus slag to silica sol, adding mercaptosilane coupling agent solution, stirring at 50-60° C. for 1-2 hours; filtering and drying to obtain modified phosphorus slag; The silicon dioxide content in the silica sol is 30-32%, the concentration of the mercaptosilane coupling agent solution is 4-5wt%; and the mass ratio of the yellow phosphorus slag, the silica sol and the mercaptosilane coupling agent solution is 1.5:0.5:1.
[0011] More optimally, the accelerating setting agent comprises aluminum sulfate and calcium carbonate in a mass ratio of (1.5-2.2): (0.5-0.8); the additive comprises modified fiber and cyclodextrin MOF in a mass ratio of (7.5-9): (0.5-1).
[0012] More optimally, the preparation method of the modified fiber is: dissolve polyvinyl alcohol in deionized water, adjust the pH to 3±0.2 with hydrochloric acid at room temperature; raise the temperature to 70~75°C, slowly add glutaraldehyde, and stir to react for 4~5 hours; cool to 60~65°C, add 3-amino-1-propanol vinyl ether and 3-carbamoylphenylboronic acid, and stir to react for 6~8 hours; add amino-modified glass fiber, continue to react for 5~6 hours, filter, wash, and dry to obtain modified fiber.
[0013] More optimally, the raw materials of the modified fiber include the following components: by weight, 10 to 12 parts of polyvinyl alcohol, 20 to 30 parts of glutaraldehyde, 3 to 6 parts of 3-amino-1-propanol vinyl ether, 1 to 2 parts of 3-carbamoylphenylboric acid, and 10 to 12 parts of amino-modified glass fiber.
[0014] More optimally, the preparation method of the cyclodextrin MOF is: add β-cyclodextrin, thiol-β-cyclodextrin and zinc chloride in a molar ratio of 0.8:0.2:8 to a 20~25wt% methanol aqueous solution in sequence, mix evenly, hydrothermally react at 60~65°C for 5~7 days, filter, wash and dry to obtain cyclodextrin MOF.
[0015] A high-strength cement prepared by a preparation process of a rapid-setting, environment-friendly, high-strength cement.
[0016] Compared with the prior art, the present application has the following beneficial effects: (1) In the scheme, phosphorus slag is used as a mineralizer and mixed with limestone, high silica, iron materials, and aluminum materials for calcination to obtain low-alkalinity cement clinker; its introduction reduces the stacking of industrial waste slag and environmental pollution. At the same time, its addition can reduce the calcination heat consumption of clinker, increase the calcination rate and clinker output; in addition, it has the function of seed crystals, which can contribute to the formation of C3S and improve the strength of clinker.
[0017] (2) In the scheme, phosphorus slag is modified with silica sol and then mixed with clinker to further improve the utilization rate of waste resources. Among them, directly adding phosphorus slag will reduce the hydration heat, which is not conducive to rapid setting and mechanical strength; silica sol modification can effectively inhibit the delayed effect of P2O5, F and other elements contained in it on the hydration of C3A; at the same time, silica sol modification can not only promote the hydration rate, but also fill the pores with silica on its surface to improve the compactness. However, the amount of introduction should not be too much, otherwise it will cause secondary hydration, produce calcium silicate gel, increase harmful pores, reduce compactness, and have an adverse effect on anti-seepage performance.
[0018] In addition, during the modification process, a mercaptosilane coupling agent was introduced to make its surface contain mercapto groups, which can be cross-linked with the modified fibers and cyclodextrin MOF in the subsequent additives in the presence of initiator AIBN using the heat generated by hydration (the cement hydration heat temperature can reach between 60°C and 80°C), thereby improving the mechanical strength of the cement after curing, such as flexural strength.
[0019] (3) In the scheme, aluminum sulfate and calcium carbonate are mixed as an accelerating agent to promote rapid setting performance. However, rapid setting performance is often accompanied by weak mechanical properties. Therefore, in the scheme, modified fibers and cyclodextrin MOF should be further added as additives to internally solidify and enhance the strength of cement.
[0020] Among them, the preparation process of the modified fiber is: the reaction grafting of the hydroxyl group in polyvinyl alcohol and the aldehyde group of glutaraldehyde, and then the aldehyde group of glutaraldehyde is used to graft 3-amino-1-propanol vinyl ether and 3-carbamoylphenylboronic acid; and the composite is obtained at the interface of amino-modified glass fiber. Among them, the reaction of hydroxyl group and aldehyde group produces N ether bonds, and at the same time, the propanol vinyl ether chain segment is introduced. The organic ether chain segment can effectively make up for the insufficient strength problem caused by the introduction of aluminum sulfate, and effectively enhance the flexural and compressive strength. At the same time, glass fiber is a common cement reinforcing material, and its direct modification can effectively enhance its dispersibility. In addition, the vinyl of propanol vinyl ether can cross-link with modified phosphorus slag; and the boric acid contained in 3-carbamoylphenylboronic acid can produce a bonding effect with calcium carbonate in the accelerator; it can also act as a water reducer to reduce viscosity and surface tension; promote early strength, reduce later damage and cracks, and improve impermeability.
[0021] Among them, cyclodextrin MOF is a hydrophilic porous framework material; its introduction can improve cement fluidity and improve mid- and late-stage strength. At the same time, it has a unique framework structure, which makes it have excellent internal curing efficiency, excellent volume stability and better interface compatibility with the cement matrix; it can prevent the formation of voids and cracks at the interface between modified fibers and cement clinker. In addition, cyclodextrin MOF can produce nano-CSH gel, thereby increasing the seed effect, which can promote the formation of hydration products, thereby facilitating the microstructure density and enhancing the mechanical strength. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are exemplified without any special restrictions: in the following embodiments, parts are parts by mass; the silica sol is a sol with a silica content of 30%; the diameter of the glass fiber is 9-13um, and the brand is Senyang; the CAS number of 3-amino-1-propanol vinyl ether is 66415-55-2; the CAS number of 3-carbamoylphenylboronic acid is 351422-73-6; the CAS number of β-cyclodextrin is 7585-39-9; the CAS number of mercapto-β-cyclodextrin is 81644-55-5; all are commercially available. In addition, among the relevant raw materials, the quality requirements for limestone are CaO≥49.0, MgO≤2.5%, and alkali content≤0.6%; the quality requirements for high-silica are SiO2≥70%, and alkali content≤1.5%; the iron material is non-ferrous metal ash, and the quality requirements are Fe2O3≥50%, and alkali content≤1.5%; the aluminum material is clay, and the quality requirements are Al2O3≤20.0; alkali content≤1.5%; the phosphorus slag is yellow phosphorus slag, and the quality requirement is CaO≥43%.
[0024] Embodiment 1: A process for preparing a rapid-setting environmentally friendly high-strength cement, comprising the following steps: Pre-preparation: (1) The preparation method of modified phosphorus slag is as follows: add yellow phosphorus slag to silica sol, add 5wt% KH-580 aqueous solution, stir at 60°C for 1 hour; filter and dry to obtain modified phosphorus slag; wherein the mass ratio of yellow phosphorus slag, silica sol and KH-580 aqueous solution is 1.5:0.5:1; (2) The preparation method of the modified fiber is as follows: glass fiber and KH-551 with a mass ratio of 1:0.2 are added to a 10wt% ethanol aqueous solution in sequence, stirred at 60°C for 2 hours, filtered and dried to obtain amino-modified glass fiber; 10 parts of polyvinyl alcohol are dissolved in 100 parts of deionized water, and the pH is adjusted to 3.1 using 0.6 mol / L hydrochloric acid solution at room temperature; the temperature is raised to 70°C, 22 parts of glutaraldehyde are slowly added dropwise, and stirred for reaction for 4 hours; the temperature is lowered to 60°C, 4.5 parts of 3-amino-1-propanol vinyl ether and 1.5 parts of 3-carbamoylphenylboronic acid are added, and stirred for reaction for 6 hours; 10 parts of amino-modified glass fiber are added, the reaction is continued for 6 hours, filtered, washed and dried to obtain modified fiber; (3) The preparation method of cyclodextrin MOF is as follows: β-cyclodextrin, thiol-β-cyclodextrin and zinc chloride in a molar ratio of 0.8:0.2:8 are added to a 25 wt % methanol aqueous solution in sequence, mixed evenly, subjected to hydrothermal reaction at 60° C. for 6 days, filtered, washed and dried to obtain cyclodextrin MOF; Step 1: Grind and mix 80 parts of limestone, 12 parts of high silica, 3 parts of iron material, 2 parts of aluminum material, and 3 parts of phosphorus slag to obtain raw material; heat the raw material to 900°C at a rate of 50°C / min, and calcine for 30 minutes; heat the raw material to 1200°C at a rate of 20°C / min, continue calcining for 10 minutes, and cool to obtain cement clinker; Step 2: Grind and mix 76.5 parts of cement clinker, 12 parts of modified phosphorus slag, 2.5 parts of accelerator (aluminum sulfate and calcium carbonate in a ratio of 2:0.5), 9 parts of additives (modified fiber, cyclodextrin MOF in a ratio of 8.4:0.6), and 0.05 parts of azobisisobutyronitrile to obtain high-strength cement.
[0025] Embodiment 2: A process for preparing a rapid-setting environmentally friendly high-strength cement, comprising the following steps: Pre-preparation: (1) The preparation method of modified phosphorus slag is as follows: add yellow phosphorus slag to silica sol, add 5wt% KH-580 aqueous solution, stir at 60°C for 1 hour; filter and dry to obtain modified phosphorus slag; wherein the mass ratio of yellow phosphorus slag, silica sol and KH-580 aqueous solution is 1.5:0.5:1; (2) The preparation method of the modified fiber is as follows: glass fiber and KH-551 with a mass ratio of 1:0.2 are added to a 10wt% ethanol aqueous solution in sequence, stirred at 60°C for 2 hours, filtered and dried to obtain amino-modified glass fiber; 10 parts of polyvinyl alcohol are dissolved in 100 parts of deionized water, and the pH is adjusted to 3.1 using 0.6 mol / L hydrochloric acid solution at room temperature; the temperature is raised to 70°C, 22 parts of glutaraldehyde are slowly added dropwise, and stirred for reaction for 4 hours; the temperature is lowered to 60°C, 4.5 parts of 3-amino-1-propanol vinyl ether and 1.5 parts of 3-carbamoylphenylboronic acid are added, and stirred for reaction for 6 hours; 10 parts of amino-modified glass fiber are added, the reaction is continued for 6 hours, filtered, washed and dried to obtain modified fiber; (3) The preparation method of cyclodextrin MOF is as follows: β-cyclodextrin, thiol-β-cyclodextrin and zinc chloride in a molar ratio of 0.8:0.2:8 are added to a 25 wt % methanol aqueous solution in sequence, mixed evenly, subjected to hydrothermal reaction at 60° C. for 6 days, filtered, washed and dried to obtain cyclodextrin MOF; Step 1: Grind and mix 78 parts of limestone, 13 parts of high silica, 2 parts of iron material, 3 parts of aluminum material, and 4 parts of phosphorus slag to obtain raw material; heat the raw material to 900°C at a rate of 50°C / min, and calcine for 30 minutes; heat the raw material to 1200°C at a rate of 20°C / min, continue calcining for 10 minutes, and cool to obtain cement clinker; Step 2: Grind and mix 72 parts of cement clinker, 10 parts of modified phosphorus slag, 2 parts of accelerator (aluminum sulfate and calcium carbonate in a ratio of 1.5:0.5), 8 parts of additives (modified fiber, cyclodextrin MOF in a ratio of 7.5:0.5), and 0.05 parts of azobisisobutyronitrile to obtain high-strength cement.
[0026] Embodiment 3: A process for preparing a rapid-setting environmentally friendly high-strength cement, comprising the following steps: Pre-preparation: (1) The preparation method of modified phosphorus slag is as follows: add yellow phosphorus slag to silica sol, add 5wt% KH-580 aqueous solution, stir at 60°C for 1 hour; filter and dry to obtain modified phosphorus slag; wherein the mass ratio of yellow phosphorus slag, silica sol and KH-580 aqueous solution is 1.5:0.5:1; (2) The preparation method of the modified fiber is as follows: glass fiber and KH-551 with a mass ratio of 1:0.2 are added to a 10wt% ethanol aqueous solution in sequence, stirred at 60°C for 2 hours, filtered and dried to obtain amino-modified glass fiber; 10 parts of polyvinyl alcohol are dissolved in 100 parts of deionized water, and the pH is adjusted to 3.1 using 0.6 mol / L hydrochloric acid solution at room temperature; the temperature is raised to 70°C, 22 parts of glutaraldehyde are slowly added dropwise, and stirred for reaction for 4 hours; the temperature is lowered to 60°C, 4.5 parts of 3-amino-1-propanol vinyl ether and 1.5 parts of 3-carbamoylphenylboronic acid are added, and stirred for reaction for 6 hours; 10 parts of amino-modified glass fiber are added, the reaction is continued for 6 hours, filtered, washed and dried to obtain modified fiber; (3) The preparation method of cyclodextrin MOF is as follows: β-cyclodextrin, thiol-β-cyclodextrin and zinc chloride in a molar ratio of 0.8:0.2:8 are added to a 25 wt % methanol aqueous solution in sequence, mixed evenly, subjected to hydrothermal reaction at 60° C. for 6 days, filtered, washed and dried to obtain cyclodextrin MOF; Step 1: Grind and mix 80 parts of limestone, 10 parts of high silica, 5 parts of iron material, 1.5 parts of aluminum material, and 3.5 parts of phosphorus slag to obtain raw material; heat the raw material to 900°C at a rate of 50°C / min, and calcine for 30 minutes; heat the raw material to 1200°C at a rate of 20°C / min, continue calcining for 10 minutes, and cool to obtain cement clinker; Step 2: Grind and mix 80 parts of cement clinker, 15 parts of modified phosphorus slag, 3 parts of accelerator (aluminum sulfate and calcium carbonate in a ratio of 2.2:0.8), 10 parts of additives (modified fiber, cyclodextrin MOF in a ratio of 9:1), and 0.05 parts of azobisisobutyronitrile to obtain high-strength cement.
[0027] Comparative Example 1: Referring to Example 1, yellow phosphorus slag is used to directly replace the modified phosphorus slag, and the rest is the same as Example 1; the specific steps are as follows: Pre-preparation: (1) The preparation method of the modified fiber is as follows: glass fiber and KH-551 with a mass ratio of 1:0.2 are added to a 10wt% ethanol aqueous solution in sequence, stirred at 60°C for 2 hours, filtered and dried to obtain amino-modified glass fiber; 10 parts of polyvinyl alcohol are dissolved in 100 parts of deionized water, and the pH is adjusted to 3.1 using 0.6 mol / L hydrochloric acid solution at room temperature; the temperature is raised to 70°C, 22 parts of glutaraldehyde are slowly added dropwise, and the mixture is stirred for reaction for 4 hours; the temperature is lowered to 60°C, 4.5 parts of 3-amino-1-propanol vinyl ether and 1.5 parts of 3-carbamoylphenylboronic acid are added, and the mixture is stirred for reaction for 6 hours; 10 parts of amino-modified glass fiber are added, the reaction is continued for 6 hours, filtered, washed and dried to obtain modified fiber; (2) The preparation method of cyclodextrin MOF is as follows: β-cyclodextrin, thiol-β-cyclodextrin and zinc chloride in a molar ratio of 0.8:0.2:8 are added to a 25 wt % methanol aqueous solution in sequence, mixed evenly, subjected to hydrothermal reaction at 60° C. for 6 days, filtered, washed and dried to obtain cyclodextrin MOF; Step 1: Grind and mix 80 parts of limestone, 12 parts of high silica, 3 parts of iron material, 2 parts of aluminum material, and 3 parts of phosphorus slag to obtain raw material; heat the raw material to 900°C at a rate of 50°C / min, and calcine for 30 minutes; heat the raw material to 1200°C at a rate of 20°C / min, continue calcining for 10 minutes, and cool to obtain cement clinker; Step 2: Grind and mix 76.5 parts of cement clinker, 12 parts of yellow phosphorus slag, 2.5 parts of accelerator (aluminum sulfate and calcium carbonate in a ratio of 2:0.5), 9 parts of additives (modified fiber, cyclodextrin MOF in a ratio of 8.4:0.6), and 0.05 parts of azobisisobutyronitrile to obtain high-strength cement.
[0028] Comparative Example 2: Referring to Example 1, the modified fiber was replaced with amino-modified glass fiber, and the rest was the same as Example 1; the specific steps were as follows: Pre-preparation: (1) The preparation method of modified phosphorus slag is as follows: add yellow phosphorus slag to silica sol, add 5wt% KH-580 aqueous solution, stir at 60°C for 1 hour; filter and dry to obtain modified phosphorus slag; wherein the mass ratio of yellow phosphorus slag, silica sol and KH-580 aqueous solution is 1.5:0.5:1; (2) The preparation method of amino-modified glass fiber is as follows: glass fiber and KH-551 in a mass ratio of 1:0.2 are sequentially added to a 10 wt % ethanol aqueous solution, stirred at 60° C. for 2 hours, filtered, and dried to obtain amino-modified glass fiber; (3) The preparation method of cyclodextrin MOF is as follows: β-cyclodextrin, thiol-β-cyclodextrin and zinc chloride in a molar ratio of 0.8:0.2:8 are added to a 25 wt % methanol aqueous solution in sequence, mixed evenly, subjected to hydrothermal reaction at 60° C. for 6 days, filtered, washed and dried to obtain cyclodextrin MOF; Step 1: Grind and mix 80 parts of limestone, 12 parts of high silica, 3 parts of iron material, 2 parts of aluminum material, and 3 parts of phosphorus slag to obtain raw material; heat the raw material to 900°C at a rate of 50°C / min, and calcine for 30 minutes; heat the raw material to 1200°C at a rate of 20°C / min, continue calcining for 10 minutes, and cool to obtain cement clinker; Step 2: Grind and mix 76.5 parts of cement clinker, 12 parts of modified phosphorus slag, 2.5 parts of accelerator (aluminum sulfate and calcium carbonate in a ratio of 2:0.5), 9 parts of additives (amino-modified glass fiber and cyclodextrin MOF in a ratio of 8.4:0.6), and 0.05 parts of azobisisobutyronitrile to obtain high-strength cement.
[0029] Comparative Example 3: Referring to Example 1, 3-amino-1-propanol vinyl ether and 3-carbamoylphenylboronic acid are not grafted into the modified fiber, and the rest is the same as Example 1; the specific steps are as follows: Pre-preparation: (1) The preparation method of modified phosphorus slag is as follows: add yellow phosphorus slag to silica sol, add 5wt% KH-580 aqueous solution, stir at 60°C for 1 hour; filter and dry to obtain modified phosphorus slag; wherein the mass ratio of yellow phosphorus slag, silica sol and KH-580 aqueous solution is 1.5:0.5:1; (2) The preparation method of the modified fiber is as follows: glass fiber and KH-551 with a mass ratio of 1:0.2 are added to a 10wt% ethanol aqueous solution in sequence, stirred at 60°C for 2 hours, filtered and dried to obtain amino-modified glass fiber; 10 parts of polyvinyl alcohol are dissolved in 100 parts of deionized water, and the pH is adjusted to 3.1 using 0.6 mol / L hydrochloric acid solution at room temperature; the temperature is raised to 70°C, 22 parts of glutaraldehyde are slowly added dropwise, and the reaction is stirred for 4 hours; the temperature is lowered to 60°C, 10 parts of amino-modified glass fiber are added, the reaction is continued for 8 hours, filtered, washed and dried to obtain modified fiber; (3) The preparation method of cyclodextrin MOF is as follows: β-cyclodextrin, thiol-β-cyclodextrin and zinc chloride in a molar ratio of 0.8:0.2:8 are added to a 25 wt % methanol aqueous solution in sequence, mixed evenly, subjected to hydrothermal reaction at 60° C. for 6 days, filtered, washed and dried to obtain cyclodextrin MOF; Step 1: Grind and mix 80 parts of limestone, 12 parts of high silica, 3 parts of iron material, 2 parts of aluminum material, and 3 parts of phosphorus slag to obtain raw material; heat the raw material to 900°C at a rate of 50°C / min, and calcine for 30 minutes; heat the raw material to 1200°C at a rate of 20°C / min, continue calcining for 10 minutes, and cool to obtain cement clinker; Step 2: Grind and mix 76.5 parts of cement clinker, 12 parts of modified phosphorus slag, 2.5 parts of accelerator (aluminum sulfate and calcium carbonate in a ratio of 2:0.5), 9 parts of additives (modified fiber, cyclodextrin MOF in a ratio of 8.4:0.6), and 0.05 parts of azobisisobutyronitrile to obtain high-strength cement.
[0030] Comparative Example 4: Referring to Example 1, cyclodextrin MOF was not introduced, and the rest was the same as Example 1; the specific steps are as follows: Pre-preparation: (1) The preparation method of modified phosphorus slag is as follows: add yellow phosphorus slag to silica sol, add 5wt% KH-580 aqueous solution, stir at 60°C for 1 hour; filter and dry to obtain modified phosphorus slag; wherein the mass ratio of yellow phosphorus slag, silica sol and KH-580 aqueous solution is 1.5:0.5:1; (2) The preparation method of the modified fiber is as follows: glass fiber and KH-551 with a mass ratio of 1:0.2 are added to a 10wt% ethanol aqueous solution in sequence, stirred at 60°C for 2 hours, filtered and dried to obtain amino-modified glass fiber; 10 parts of polyvinyl alcohol are dissolved in 100 parts of deionized water, and the pH is adjusted to 3.1 using 0.6 mol / L hydrochloric acid solution at room temperature; the temperature is raised to 70°C, 22 parts of glutaraldehyde are slowly added dropwise, and stirred for reaction for 4 hours; the temperature is lowered to 60°C, 4.5 parts of 3-amino-1-propanol vinyl ether and 1.5 parts of 3-carbamoylphenylboronic acid are added, and stirred for reaction for 6 hours; 10 parts of amino-modified glass fiber are added, the reaction is continued for 6 hours, filtered, washed and dried to obtain modified fiber; Step 1: Grind and mix 80 parts of limestone, 12 parts of high silica, 3 parts of iron material, 2 parts of aluminum material, and 3 parts of phosphorus slag to obtain raw material; heat the raw material to 900°C at a rate of 50°C / min, and calcine for 30 minutes; heat the raw material to 1200°C at a rate of 20°C / min, continue calcining for 10 minutes, and cool to obtain cement clinker; Step 2: Grind and mix 76.5 parts of cement clinker, 12 parts of modified phosphorus slag, 2.5 parts of accelerating agent (aluminum sulfate and calcium carbonate in a ratio of 2:0.5), 9 parts of modified fiber, and 0.05 parts of azobisisobutyronitrile to obtain high-strength cement.
[0031] Performance test: The high-strength cement prepared in the embodiment and the comparative example was subjected to relevant performance tests; wherein, the initial setting time and the final setting time were tested according to the relevant standard of GB / T1346; and the compressive strength after 3 days and 28 days was tested according to the relevant standard of GB / T17671; the obtained data are shown in the following table: sample Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Initial setting time (min) 82 93 91 87 86 Final setting time (min) 321 413 387 348 365 3d compressive strength (MPa) 28.2 24.3 24.9 25.6 25.9 28d compressive strength (MPa) 56.7 48.0 49.1 50.7 50.3 Conclusion: From the data in the above table, we can see that: through the silica sol pre-modification process of yellow phosphorus slag, the specific grafting chain segments of modified fibers, and the introduction of cyclodextrin MOF, and the use of the heat generated during the hydration process to initiate the cross-linking structure-activity relationship of related materials, the mechanical strength such as compressive strength is effectively enhanced on the basis of ensuring the rapid setting performance of cement. At the same time, the scheme effectively utilizes phosphorus slag waste, increases resource utilization, and improves environmental protection.
[0032] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing fast-setting environmentally friendly high-strength cement, characterized in that: The following steps are involved: Step 1: Grind and mix limestone, high silica, iron material, aluminum material, and phosphorus slag to obtain raw material; calcine the raw material, cool it, and obtain cement clinker; Step 2: Grind and mix cement clinker, modified phosphorus slag, accelerator, additive and azobisisobutyronitrile to obtain high-strength cement.
2. The process for preparing a rapid-setting, environment-friendly, high-strength cement according to claim 1, characterized in that: The calcination process parameters are: heating to 800-1000°C at a rate of 40-50°C / min, calcining for 10-30 minutes; heating to 1150-1250°C at a rate of 20-30°C / min, and continuing calcining for 10-15 minutes.
3. The process for preparing a rapid-setting, environment-friendly, high-strength cement according to claim 1, characterized in that: The raw materials of the cement clinker include the following components: by weight, 78-82 parts of limestone, 10-13 parts of high silica, 2-5 parts of iron materials, 1.5-3 parts of aluminum materials, and 3-4 parts of phosphorus slag.
4. The process for preparing a rapid-setting, environment-friendly, high-strength cement according to claim 1, characterized in that: The high-strength cement comprises the following raw materials: by weight, 72-80 parts of cement clinker, 10-15 parts of modified phosphorus slag, 2-3 parts of accelerating agent, 8-10 parts of additives, and 0.05-0.06 parts of azobisisobutyronitrile.
5. The process for preparing a rapid-setting, environment-friendly, high-strength cement according to claim 1, characterized in that: The preparation method of the modified phosphorus slag is as follows: adding yellow phosphorus slag to silica sol, adding mercaptosilane coupling agent solution, stirring at 50-60° C. for 1-2 hours; filtering and drying to obtain the modified phosphorus slag; The silicon dioxide content in the silica sol is 30-32%, the concentration of the mercaptosilane coupling agent solution is 4-5wt%; and the mass ratio of the yellow phosphorus slag, the silica sol and the mercaptosilane coupling agent solution is 1.5:0.5:
1.
6. The process for preparing a rapid-setting, environment-friendly, high-strength cement according to claim 1, characterized in that: The accelerating setting agent comprises aluminum sulfate and calcium carbonate in a mass ratio of (1.5-2.2): (0.5-0.8); the additive comprises modified fiber and cyclodextrin MOF in a mass ratio of (7.5-9): (0.5-1).
7. The process for preparing a rapid-setting, environment-friendly, high-strength cement according to claim 6, characterized in that: The preparation method of the modified fiber is as follows: polyvinyl alcohol is dissolved in deionized water, and hydrochloric acid is used to adjust the pH value to 3±0.2 at room temperature; the temperature is raised to 70-75°C, glutaraldehyde is slowly added dropwise, and the mixture is stirred for reaction for 4-5 hours; the temperature is lowered to 60-65°C, 3-amino-1-propanol vinyl ether and 3-carbamoylphenylboronic acid are added, and the mixture is stirred for reaction for 6-8 hours; amino-modified glass fiber is added, the reaction is continued for 5-6 hours, and the modified fiber is obtained by filtering, washing, and drying.
8. The process for preparing a rapid-setting, environment-friendly, high-strength cement according to claim 7, characterized in that: The raw materials of the modified fiber include the following components: by weight, 10-12 parts of polyvinyl alcohol, 20-30 parts of glutaraldehyde, 3-6 parts of 3-amino-1-propanol vinyl ether, 1-2 parts of 3-carbamoylphenylboric acid, and 10-12 parts of amino-modified glass fiber.
9. The process for preparing a rapid-setting, environment-friendly, high-strength cement according to claim 6, characterized in that: The preparation method of the cyclodextrin MOF is as follows: β-cyclodextrin, mercapto-β-cyclodextrin and zinc chloride in a molar ratio of 0.8:0.2:8 are sequentially added to a 20-25wt% methanol aqueous solution, mixed evenly, subjected to hydrothermal reaction at 60-65° C. for 5-7 days, filtered, washed and dried to obtain the cyclodextrin MOF.
10. High-strength cement prepared according to the process for preparing rapid-setting, environment-friendly high-strength cement according to any one of claims 1 to 9.
Citation Information
Patent Citations
Process for producing clinker by using yellow phosphorus slag as mineralizer
CN111574077A
Quick-setting environment-friendly high-strength cement and preparation method thereof
CN115925349A
Rapid setting high strength calcium phosphate cements comprising cyclodextrins
US20110073006A1
Cited By
Preparation method of viscosity reduction type polycarboxylic acid high-performance water reducing agent
CN120622841A